Implementasi Quick Response Code (QR Code) Untuk Administrasi Berbasis Digital Pada Laboratorium Mekanika Tanah FT Unnes - Nuraida; Nurul Yuhanafia; Arief Kusbiantoro (Aptek, 2025)
Along with technological advancements, many universities have begun implementing digital-based laboratory administration systems to improve data efficiency and accuracy. However, conventional processes for borrowing laboratory equipment still pose challenges, particularly in terms of record-keeping and data security. This study aims to develop a digital-based Soil Mechanics Laboratory Management System (SIMPALTAN) using the Google Sites platform integrated with Quick Response (QR) Codes. The system is designed to facilitate the borrowing and use of laboratory equipment. Testing was conducted to measure the effectiveness of QR Code usage in improving administrative efficiency. The results indicate that the implementation of QR Codes significantly accelerates the administrative process compared to conventional methods, making this system a viable solution for use in educational laboratory environments.